Intervenções familiares na esquizofrenia: dos aspectos teóricos à situação em Portugal - Gonçalves-Pereira, M (2006)
In the field of pychoeducational interventions in schizophrenia, terminology is sometimes misleading and further efforts are needed to specify and operationalise terms such as psychoeducation or family intervention, especially wherever they are adapted, for example, for use in non-English speaking countries. On the other hand, in spite of growing evidence of their clinical effectiveness, family interventions for schizophrenia are still not routinely implemented in real life clinical settings. Furthermore, the current poverty of original literature or replication studies in Portugal in the field of family interventions is astonishing. Several high-quality review papers have been published in the last two decades, summarising or meta-analysing data concerning efficacy, effectiveness and efficiency of these family interventions worldwide, but mostly in Anglo-Saxon literature. These findings were indeed incorporated in several clinical guidelines, namely in the United Kingdom. But there seems to exist, in a considerable number of settings, a lack of will to implement scientific findings established for more than twenty years. In developed countries, this should be addressed as a true paradox.